Pengaruh personal branding, tingkat kepuasan, trust, dan motivasi berkoperasi terhadap loyalitas anggota Koperasi Simpan Pinjam Pembiayaan Syariah (KSPPS) “Bina Bersama” Lampung Utara - Miswanto , Miswanto; Sirait, Dian Rumintang Irianti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of personal branding, level of satisfaction, trust, and motivation of cooperatives on the loyalty of members of the Sharia Financing Savings and Loans Cooperative "Bina Bersama" North Lampung. This research is causal quantitative research. The dependent variable is loyalty and the independent variables are personal branding, level of satisfaction, trust, and motivation to cooperate. This research sample amounted to 166 samples taken by non-probability sampling technique with purposive sampling. Based on the results of the study, it was found that: (1) there is a positive influence of personal branding on the loyalty of cooperative members (2) there is no influence of the level of satisfaction on the loyalty of cooperative members (3) there is a positive influence of trust on the loyalty of cooperative members (4) there is no positive effect of cooperative motivation to the loyalty of cooperative members.